Discriminant analysis of the equicorrelated Gaussian observations - Dučinskas, Kęstutis; Neverdauskaiė, Jurgita (Lietuvos matematikos rinkinys, 2021)
In this paper the problem of classification of an observation into one of two Gaussian populations with different means and common variance is considered in the case when equicorrelated training sample is given. Unknown means and common variance are estimated from training sample and these estimators are pluged in the Bayes discriminant function. The maximum likelihood estimators are used. The approximation of the expected error rate associated with Bayes plug-in discriminant function is derived. Numerical analysis of the accuracy of that approximation for various values of correlation is presented.
Keywords: equicorrelation; Bayes discriminant function; actual error rate; expected error rate